Determining the presence and concentration of Lead (Pb) and Cadmium (Cd) in sediments and shellfishes in Isabel, Leyte - Calibuso, Alfred B.; dela Cruz, Margarita T. (Tacloban City Division of Natural Sciences and Mathematics, Universityof the Philippines Visayas Tacloban City, 2009)
Lead (Pb) and Cadmium (Cd) concentrations in sediments and soft tissues of shellfishes (Katalysia japonica, Terebralia sulcata, and Clypeomorus sp.) were determined to assess the environmental-condition-of-Isabel, Leyte, in terms of these heavy metals In addition, the concentrations-of-Pb-and-Ed-in-the-mollusks-wer computed for the Maximum Recommended Yearly Consumption (MRYC) (kg/year), in station the safety of these shellfishes as human food. Results showed that the nig concentration of Pb (94 ppm) and Cd (4.86 ppm)/in sediments were found (Bgy. Matlang). The lov lowest concentration of Pb (42 ppm) and Cd (1.93 ppm) in sediments were detected in station 1 (Bgy. Bantigue). Furthermore, the highest concentration of Pb (7 ppm in Terabralia sulcata) and Cd (4.86 ppm in Katalysia japonica) in the soft tissues of mollusks were found in station 2 and 3, respectively. The lowest concentration of Pb (4.33 ppm) and Cd (1.933 ppm) were detected in Katalysia samples of station 1. Comparison between-Pb-and-Ed-concentrations-in-the-shellfish samples was not-recommended due to the non-homogenous samples across different stations, In conclusion, the concentrations of Pb and Cd in the sediments of Isabel, Leyte were determined to be above the Threshold Effect Level (TEL), indicative of non-toxic to toxic effect of heavy metals to sedentary organisms. The computed MRYC for Pb in Katalysia japonica (station 1) were 0.5255, 2.065, and 6.308 kg/year for children, pregnant women, and adult, respectively. The MRYC value for Terabralia sulcata in children, pregnant women, and adult were 0.3249, 1.277 and 3.894 kg/year, respectively. For Clypeomorus sp., the levels of MRYC were computed to be 0.4549, 1.789, and 5.467 kg/year. Moreover, the MRYCs for Cadmium in Katalysia japonica were 2.092 and 30.51 kg/year for children and adult. For Terebralia sulcata, the MRYCS were 1.557 and 22.71 kg/year for children and adult. The MRYCs for Clypeomorus sp. for children and adults were 1.401 and 20.44 kg/year, respectively.
Undergraduate thesis (Bachelor of Science in Biology) -- University of the Philippines, Tacloban.